The use of açaí as a potential antioxidant for bovine semen cryopreservation - Barros Luz, Janaina; Oliveira Sampaio, Luis Rennan; Crespilho, André Maciel; Gomes, Daiany Íris; Araújo Andrade, Mariana; Travassos Vieira, Joane Isis; Chaves, Maiana Silva; Lima Basto, Sarah Romini; Souza Alves, Kaliandra (Medicina Veterinária, 2019)
Semen cryopreservation is an important tool for animal reproduction due to its potential for fast dissemination of genetics from males with high genetic merit. However, cryopreservation protocols continue to provoke negative effects on sperm cell structure and function, thus leading to lower viability. This reduction in viability is correlated with excessive production of reactive oxygen species (ROS) that generate oxidative stress, which is responsible for lowering sperm motility, alteration in plasma membrane fluidity, and lipidic peroxidation. Due to these facts, it becomes necessary to add substances with the antioxidant potential for semen cryopreservation to confer additional protection to sperm cells. A variety of compounds from plants and fruits have been incorporated to such media due to their antioxidant potential. In such context, açaí has gained attention by researchers due to its substantial antioxidant capacity, particularly attributed to its polyphenolic fraction, which is rich in anthocyanins. Moreover, it also contains resveratrol and quercetin in its composition, which has activity against free radicals. In general terms, the antioxidant of natural sources (i.e., açaí) deserves special attention since it contributes to the preservation of the national flora, also displays a significant potential to improve the quality of frozen-thawed bovine semen.